Obraz cesarza Juliana Apostaty w panegiryku Klaudiusza Mamertinusa - Pająkowska-Bouallegui, Anna (Instytut Historyczny Uniwersytetu Wrocławskiego, 2023)
Julian the Apostate, the Roman ruler from 361 to 363, was an extraordinary figure in the history of the Roman Empire. His close associate, Claudius Mamertinus, was granted the honor of a consulship by the emperor in 362. To thank him for that great distinction, Claudius wrote a panegyric – Gratiarum actio Mamertini de consulatu suo Iuliano Imperatori (A speech of thanks to the Emperor Julian given by Claudius Mamertinus on the occasion of his elevation to the Consulate) – in honor of the ruler. The speech by Claudius Mamertinus is a very important source of information about the history of Julian the Apostate. It shows the nobility of his character, his full dedication to the public good, and that one life that can be a model for many. This speech of thanks is also a kind of a political manifesto. It displays Julian's political program in relation to the capital, the provinces, the Senate, and the Consuls. Claudius Mamertinus' panegyric has special features that deserve careful study because of their literary and historical value.
Keywords: Julian Apostata; Klaudiusz Mamertinus; Podziękowanie dla cesarza Juliana za konsulat